Dye-sensitive solar cell based on composite structure photoanode and its preparation method and application
By using Au/SnS/TiO2 composite structured photoanode and natural dyes in dye-sensitive solar cells, the problems of insufficient utilization of light with low wavelengths and high production costs in the prior art are solved, efficient photoelectric conversion and stability are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202210515475.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-05-11
AI Technical Summary
Existing dye-sensitive solar cells fail to effectively utilize light at longer wavelengths and lower energy portions, and use expensive synthetic dyes and platinum counter electrodes, resulting in high production costs.
The Au/SnS/TiO2 composite structured photoanode and natural dyes were used to prepare dye-sensitive solar cells by spin coating and high temperature calcination. The low band gap width of SnS and the high band gap width of TiO2 were used to absorb light of different wavelengths, and the photoanode performance was enhanced by the plasmon resonance effect of Au nanoparticles.
It improves the photoelectric conversion efficiency and stability, reduces production costs, expands the light absorption range, reduces electronic recombination, and achieves more efficient light energy utilization.
Smart Images

Figure CN115064388B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a dye-sensitive solar cell based on a composite structure photoanode and a preparation method and application thereof. Background Art
[0002] The development of new energy technology has greatly reduced the use of fossil energy, and solar cells, as an important component of new energy technology, have been widely used in social life. Compared with traditional silicon-based solar cells, dye-sensitized solar cells are increasingly favored by the market due to their lower production costs, higher theoretical photoelectric conversion efficiency, and especially their natural light-transmitting properties.
[0003] The development of new energy technologies has also led to the rapid development of the electric vehicle industry. However, at present, charging electric vehicles is far less convenient and quick than refueling fuel vehicles. The inconvenient problem of charging electric vehicles needs to be solved urgently. Compared with building more charging piles, the problem of inconvenient charging can be solved from the electric vehicle itself. The traditional electric vehicle sunroof only has functions such as light transmission, ventilation, and beauty, which greatly wastes the advantage of the large area of the electric vehicle sunroof. Therefore, taking advantage of the light-transmitting and power-generating advantages of dye-sensitive solar cells, dye-sensitive solar cells are integrated into the original car sunroof, making full use of the large area of the car sunroof, and charging the electric vehicle as long as it is in the sun.
[0004] Most existing dye-sensitive solar cells ignore the absorption and utilization of light with longer wavelengths and lower energy. The photoanode should be improved to utilize this part of light. In addition, the dyes are generally synthetic dyes with complex preparation methods and are very expensive. The counter electrode is also usually an expensive platinum counter electrode, which greatly increases the production cost of dye-sensitive solar cells.
[0005] The invention patent with publication number CN102360958B discloses a ZnS / Au / TiO2 nanocomposite film photoanode, which exhibits excellent photogenerated cathode protection effect. However, since the bandgap widths of ZnS and TiO2 in the ZnS / Au / TiO2 photoanode are relatively high, it cannot absorb and utilize the light with longer wavelength and lower energy, resulting in a waste of this part of light resources. In addition, the Au layer is blocked by ZnS and cannot fully play the role of the local surface plasmon resonance effect of the Au layer, so that the Au layer has limited enhancement of the photoanode performance. Summary of the invention
[0006] In view of the above-mentioned problems, the present invention aims to provide a dye-sensitive solar cell based on a composite structure photoanode, and a preparation method and application thereof. The dye-sensitive solar cell prepared by spin coating and high-temperature calcination using Au / SnS / TiO2 composite structure photoanode and natural dyes has good photoelectric conversion efficiency and stability. When applied to the sunroof of an electric car, it can not only retain the function of the original car sunroof, but also generate electricity to charge the car.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] The method for preparing a dye-sensitive solar cell based on a composite structure photoanode is characterized by comprising the following steps:
[0009] S1: Preparation of Au / SnS / TiO2 composite structure photoanode;
[0010] S2: preparing electrolyte solution;
[0011] S3: preparing blueberry juice with natural dye;
[0012] S4: preparing the counter electrode;
[0013] S5: Assemble the Au / SnS / TiO2 composite structure photoanode, electrolyte, natural dye and counter electrode into a dye-sensitive solar cell.
[0014] Furthermore, the specific operation of step S1 includes the following steps:
[0015] S101: Clean the conductive glass and air-dry it for later use;
[0016] S102: preparing titanium dioxide slurry, NaS solution, SnCl2 solution and Au nano solution for later use;
[0017] S103: evenly spin-coating the titanium dioxide slurry onto the surface of the conductive glass, heating to 400-500° C. and calcining for 2 h at a heating rate of 6-8° C. / min;
[0018] S104: using NaS solution and SnCl2 solution, a SnS layer is prepared on the surface of the conductive glass coated with titanium dioxide slurry by a continuous ion layer adsorption reaction method;
[0019] S105: Use a dropper to evenly drop the Au nano-solution onto the conductive glass treated in step S104. After natural air drying, anneal at 80-120°C for 2-5 minutes at a heating rate of 15-25°C / s to finally obtain an Au / SnS / TiO2 composite structure photoanode.
[0020] Furthermore, the method for preparing the titanium dioxide slurry in step S102 comprises the following steps:
[0021] S1021a: Accurately weigh 0.15g polyvinyl pyrrolidone powder and 0.3g P 25 -Put the TiO2 powder in a beaker and stir to mix the two solids evenly;
[0022] S1022a: Add 1 mL of anhydrous ethanol and 1 mL of deionized water to the beaker in step S1021a, and stir with a glass rod until completely mixed to obtain titanium dioxide slurry.
[0023] Further, the method for preparing the SnCl2 solution described in step S102 comprises the following steps:
[0024] S1021b: Mix dihydrate SnCl2 and concentrated hydrochloric acid in a ratio of 1:5:
[0025] S1022b: The mixed solution in step S1021b is continuously heated at a temperature of 100° C. until the solution changes from turbid to clear and transparent, and then deionized water is added to prepare a 0.01 mol / L SnCl2 solution.
[0026] Furthermore, the method for preparing the Au nano-solution in step S102 comprises the following steps:
[0027] S1021c: Accurately weigh 0.1 g of sodium citrate and add it to a beaker containing 10 mL of deionized water. Use a glass rod to stir until the sodium citrate is completely dissolved to obtain a sodium citrate solution.
[0028] S1022c: Accurately weigh 0.01 g of solid tetrachloroauric acid, add it to a beaker containing 100 mL of deionized water, and heat to boiling while stirring;
[0029] S1023c: Measure 2 mL of the sodium citrate solution in step S1021c, add it to the beaker in step S1022c, continue stirring and heating for 10 minutes, then remove the heat source and continue stirring for 15 minutes, cool to room temperature, and obtain an Au nano solution rich in Au nanoparticles.
[0030] Furthermore, the specific operation of step S2 includes the following steps:
[0031] S201: Accurately weigh 0.635 g of iodine and add it to a beaker containing 10 mL of ethylene glycol, stirring until completely dissolved;
[0032] S202: Accurately weigh 1.66 g of potassium iodide and add it to a beaker containing 10 mL of ethylene glycol, stirring until completely dissolved;
[0033] S203: 1 mL of the solutions in steps S201 and S202 are measured respectively, and mixed to obtain an electrolyte solution.
[0034] Furthermore, the specific operation of step S4 includes the following steps:
[0035] S401: ultrasonically clean the conductive glass using acetone, ethanol and deionized water respectively, and air dry;
[0036] S402: A graphite layer is uniformly coated on the surface of the air-dried conductive glass to obtain a counter electrode.
[0037] Furthermore, the specific operation of step S5 includes the following steps:
[0038] S501: placing the Au / SnS / TiO2 composite structure photoanode prepared in step S1 in the natural dye prepared in step S3, soaking for 24 hours, taking it out and rinsing the surface of the Au / SnS / TiO2 composite structure photoanode with deionized water;
[0039] S502: clamping the Au / SnS / TiO2 composite structure photoanode processed in step S501 and the counter electrode prepared in step S4 together with a clamp;
[0040] S503: Use a pipette to absorb the electrolyte solution prepared in step S2, and inject it into the gap between the Au / SnS / TiO2 composite structure photoanode and the counter electrode, and wait for the electrolyte solution to diffuse into the entire gap space to complete the assembly of the dye-sensitive solar cell.
[0041] Furthermore, a dye-sensitive solar cell is prepared using a method for preparing a dye-sensitive solar cell based on a composite structure photoanode.
[0042] Furthermore, the dye-sensitive solar cell prepared by the method for preparing the dye-sensitive solar cell based on the composite structure photoanode is used in the sunroof of an electric vehicle.
[0043] The beneficial effects of the present invention are as follows: compared with the prior art, the improvement of the present invention is that:
[0044] 1. The preparation method of the dye-sensitive solar cell based on the composite structure photoanode in the present invention is to prepare the Au / SnS / TiO2 composite structure photoanode on the clean conductive glass surface by spin coating, continuous ion layer adsorption reaction method, natural deposition and the like, and use iodine, potassium iodide and ethylene glycol to prepare I-rich - and I3 - The electrolyte is prepared by coating the clean FTO surface with carbon rods to prepare the counter electrode, and finally assembled together to form a dye-sensitive solar cell based on a composite structure photoanode and natural dye sensitization. After testing, the dye-sensitive solar cell has good photoelectric conversion efficiency and working stability.
[0045] 2. The SnS in the Au / SnS / TiO2 photoanode in this application has a relatively low bandgap, and can absorb and utilize light with a longer wavelength and lower energy. The TiO2 has a relatively high bandgap, and can absorb and utilize light with a shorter wavelength and higher energy, and has a wider range of light absorption and utilization. In addition, the Au nanoparticles are not blocked, and the localized surface plasmon resonance effect of the Au nanoparticles can be fully utilized, thereby enhancing the performance of the photoanode.
[0046] 3. The composite structure photoanode and natural dye-sensitized dye-sensitive solar cells prepared by the preparation method of the present invention greatly save the production cost compared with the traditional silicon-based solar cells, and the semi-transparent characteristics of the dye-sensitized solar cells are also not possessed by the traditional silicon-based cells. Compared with the traditional dye-sensitized solar cells, the photoanode of the dye-sensitized solar cell in the present invention has a larger specific surface area, which can adsorb more dyes and increase the number of photogenerated electrons. Compared with the synthetic dyes with complex preparation methods, the use of natural dyes is non-toxic, environmentally friendly and cost-saving; due to the lower bandgap of SnS, the light absorption range of the photoanode is expanded, the movement of electrons is promoted, and the electron recombination is reduced. The use of carbon counter electrodes instead of traditional platinum counter electrodes also reduces the manufacturing cost.
[0047] 4. The dye-sensitive solar cell based on the composite structure photoanode and natural dye sensitization in the present invention can be integrated into the original sunroof of the electric vehicle. By virtue of the natural light-transmitting property of the dye-sensitive solar cell, the integrated car sunroof can retain its original function; and, no matter whether the electric vehicle is driving or stationary, as long as it is in the sun, the car can be charged by means of the dye-sensitive solar cell integrated in the sunroof, which greatly reduces the use cost of the electric vehicle, reduces the charging time and the trouble of queuing for charging at the charging pile. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The present invention is a flow chart of the method for preparing a dye-sensitive solar cell based on a composite structure photoanode.
[0049] Figure 2 It is a schematic diagram of the structure of a dye-sensitive solar cell based on a composite structure photoanode of the present invention.
[0050] Figure 3 This is a SEM image of the nano-TiO2 layer prepared in the present invention.
[0051] Figure 4 This is a SEM image of the nano SnS / TiO2 layer prepared in the present invention.
[0052] Figure 5 This is a SEM image of the nano-Au / SnS / MoS2 layer prepared in the present invention.
[0053] Figure 6 Graph showing the photocurrent responses of photoanodes with different composite structures in the present invention.
[0054] Figure 7 The electrochemical impedance spectroscopy test results of the photoanodes with different composite structures in the present invention are shown.
[0055] Figure 8 The performance test results of dye-sensitive solar cells assembled using photoanodes with different composite structures according to the present invention are shown.
[0056] Fig. 9 This is a schematic diagram of the application of the dye-sensitive solar cell based on the composite structure photoanode in the present invention in the automobile sunroof. DETAILED DESCRIPTION
[0057] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0058] As attached Figure 1 As shown, the method for preparing a dye-sensitive solar cell based on a composite structure photoanode includes the following steps:
[0059] S1: Preparation of Au / SnS / TiO2 composite structure photoanode;
[0060] Specifically, S101: using acetone, ethanol, and deionized water to ultrasonically clean the conductive glass (FTO) for 2 minutes respectively, and then using a high-temperature blower to air-dry at 60° C.;
[0061] Further, S102: preparing titanium dioxide slurry, NaS solution, SnCl2 solution and Au nano solution for standby use;
[0062] The method for preparing titanium dioxide slurry comprises the following steps:
[0063] S1021a: Accurately weigh 0.15 g polyvinyl pyrrolidone powder and 0.3 g P 25 -Put the TiO2 powder in a beaker and stir to mix the two solids evenly;
[0064] S1022a: Add 1 mL of anhydrous ethanol and 1 mL of deionized water to the beaker in step S1021a, and stir with a glass rod for 2 min until completely mixed to obtain titanium dioxide slurry.
[0065] The preparation method of the NaS solution is specifically as follows: NaS solid and deionized water are mixed and fully stirred until the NaS is completely dissolved to prepare a 0.01 mol / L NaS solution.
[0066] The preparation method of SnCl2 solution comprises the following steps:
[0067] S1021b: Mix dihydrate SnCl2 and concentrated hydrochloric acid in a ratio of 1:5:
[0068] S1022b: The mixed solution in step S1021b is continuously heated at a temperature of 100° C. until the solution changes from turbid to clear and transparent, and then deionized water is added to prepare a 0.01 mol / L SnCl2 solution.
[0069] The preparation method of Au nano solution comprises the following steps:
[0070] S1021c: Accurately weigh 0.1 g of sodium citrate and add it to a beaker containing 10 mL of deionized water. Use a glass rod to stir until the sodium citrate is completely dissolved to obtain a sodium citrate solution.
[0071] S1022c: Accurately weigh 0.01 g of solid tetrachloroauric acid, add it to a beaker containing 100 mL of deionized water, and heat to boiling while stirring;
[0072] S1023c: Measure 2 mL of the sodium citrate solution in step S1021c, add it to the beaker in step S1022c, continue stirring and heating for 10 minutes, then remove the heat source and continue stirring for 15 minutes, cool to room temperature, and obtain an Au nano solution rich in Au nanoparticles.
[0073] Further, S103: spin-coating the titanium dioxide slurry onto the surface of the conductive glass at a rotation speed of 2400 r / min for a spin coating time of 1 min, and repeating this step twice; then heating the FTO spin-coated with the titanium dioxide slurry to 450° C. and calcining for 2 h in a box-type resistance furnace at a heating rate of 7.5° C. / min;
[0074] Further, S104: using NaS solution and SnCl2 solution, using continuous ion layer adsorption reaction method (SILAR) to prepare SnS layer on the surface of conductive glass coated with titanium dioxide slurry; the specific operation is: immersing the conductive glass calcined in step S103 in NaS solution for 1 minute, taking it out and rinsing it with deionized water for 5 seconds, and air-drying it at 60°C using a high-temperature blower; then immersing it in SnCl2 solution for 1 minute, taking it out and rinsing it with deionized water for 5 seconds, and air-drying it at 60°C using a high-temperature blower; repeating the operation 4 times, and then annealing the air-dried conductive glass at 250°C for 3 minutes using a rapid annealing system, with a heating rate of 20°C / s;
[0075] Further, S105: use a dropper to evenly drop the Au nano solution onto the conductive glass treated in step S104, and after natural air drying, use a rapid annealing system to anneal at 100°C for 3 minutes with a heating rate of 20°C / s, and finally obtain an Au / SnS / TiO2 composite structure photoanode.
[0076] Furthermore, S2: preparing an electrolyte solution;
[0077] Specifically, S201: accurately weigh 0.635 g of iodine and add it to a beaker containing 10 mL of ethylene glycol, and stir until it is completely dissolved;
[0078] S202: Accurately weigh 1.66 g of potassium iodide and add it to a beaker containing 10 mL of ethylene glycol, stirring until completely dissolved;
[0079] S203: 1 mL of the solutions in steps S201 and S202 are measured respectively, and mixed to obtain an electrolyte solution.
[0080] Furthermore, S3: preparing natural dye blueberry juice;
[0081] Specifically, the purchased blueberry fruits are fully ground, the ground blueberry fruits are filtered with gauze, and the filtered blueberry juice is collected in a beaker to obtain the natural dye blueberry juice.
[0082] Furthermore, S4: preparing a counter electrode;
[0083] Specifically, S401: using acetone, ethanol, and deionized water to ultrasonically clean the conductive glass (FTO) for 2 minutes respectively, and then using a high-temperature blower to air-dry at 60° C.;
[0084] S402: Use a carbon rod to evenly coat a graphite layer on the surface of the air-dried conductive glass to obtain a counter electrode.
[0085] Furthermore, S5: the Au / SnS / TiO2 composite structure photoanode, electrolyte, natural dye and counter electrode are assembled into a dye-sensitive solar cell.
[0086] Specifically, S501: placing the Au / SnS / TiO2 composite structure photoanode prepared in step S1 in the natural dye prepared in step S3, soaking for 24 hours, so that the dye is adsorbed on the surface of the Au / SnS / TiO2 composite structure photoanode as much as possible, and then taking it out and rinsing the surface of the Au / SnS / TiO2 composite structure photoanode with deionized water to remove excess impurities;
[0087] S502: clamping the Au / SnS / TiO2 composite structure photoanode processed in step S501 and the counter electrode prepared in step S4 together with a clamp;
[0088] S503: Use a pipette to absorb the electrolyte solution prepared in step S2, and inject it into the gap between the Au / SnS / TiO2 composite structure photoanode and the counter electrode, and wait for the electrolyte solution to diffuse into the entire gap space to complete the assembly of the dye-sensitive solar cell.
[0089] The structure of the dye-sensitive solar cell in the present invention is as shown in the attached figure. Figure 2 As shown in the attached Figure 2 In the figure, the left side is a composite structure photoanode with FTO as the substrate, the right side is a counter electrode with FTO as the substrate, and the middle of the electrode is I-rich - and I3 - The working principle of the dye-sensitive solar cell is:
[0090] When light is irradiated onto the photoanode surface, the natural dye molecules (D) are first excited (D * ),
[0091] D+hv→D *
[0092] In the excited state (D * ) dye molecules inject electrons into the conduction band of the semiconductor layer composed of SnS / TiO2, D * →D + +e - (CB);
[0093] The electrons then diffuse to the conductive substrate FTO and diffuse to the external circuit to generate current, and then the dye molecules in the oxidized state (D + ) can be obtained by I in the electrolyte - Oxidized to I3 - And regenerate.
[0094]
[0095] Electrolyte oxidation state I3 - It is then reduced to I at the counter electrode. - This forms a cycle.
[0096]
[0097] When light with energy greater than the bandgap of TiO2 (about 3.2 eV) is irradiated onto the TiO2 surface, photoexcited electrons jump from the valence band to the conduction band, leaving holes in the valence band. The electric field formed promotes the flow of electrons injected by the dye molecules.
[0098] The bandgap width of SnS (about 1.01eV) is much smaller than that of TiO2, so some light with lower energy and longer wavelength can excite electrons inside SnS, enhancing the utilization rate of light by the photoanode.
[0099] When light shines on the surface of Au particles, it triggers the surface plasmon effect, which generates a strong electric field near the Au particles, enhancing the conductivity and electron transfer efficiency of the photoanode.
[0100] Performance test results:
[0101] The titanium dioxide (TiO2) layer on the surface of the conductive glass in step S103, the SnS / TiO2 layer on the surface of the conductive glass in step S104, and the Au / SnS / TiO2 layer on the surface of the conductive glass in step S105 were characterized. The specific characterization method adopts the existing characterization method, which is not described in detail in this application. The characterization results are as follows:
[0102] The SEM image of the TiO2 layer is shown in the attached Figure 3 As shown in the attached Figure 3 Uniformly arranged spherical nano-TiO2 arrays can be observed. The rough surface composed of countless TiO2 nano-sphere particles is more conducive to the attachment of other substances, and the close connection of nano-sphere particles is also conducive to the transmission of electrons.
[0103] The SEM image of SnS / TiO2 layer is shown in the attached figure. Figure 4 As shown in the attached Figure 4 It can be observed that irregular SnS nanoparticles are attached to the surface of uniformly arranged spherical nano-TiO2 arrays.
[0104] The SEM image of Au / SnS / TiO2 layer is shown in the attached figure. Figure 5 As shown in the attached Figure 5 A small amount of Au nanoparticles can be observed dotted on the surface of the SnS / TiO2 layer, eventually forming a composite structure of Au / SnS / TiO2.
[0105] Furthermore, performance tests were performed on the conductive glass with a titanium dioxide (TiO2) layer on the surface in step S103 (TiO2 photoanode), the conductive glass with a SnS / TiO2 layer on the surface in step S104 (SnS / TiO2 photoanode), and the conductive glass with an Au / SnS / TiO2 layer on the surface in step S105 (Au / SnS / TiO2 composite structure photoanode).
[0106] The photocurrent response results of different photoanodes under 365nm ultraviolet light source are shown in the attached figure. Figure 6 As shown in the attached Figure 6It can be seen that different photoanodes exhibit different photocurrent responses under the irradiation of a 365nm violet light source, and the photocurrent responses of different photoanodes are relatively stable in the test lasting 170S, among which the photocurrent response of the Au / SnS / TiO2 photoanode is the strongest, indicating that the Au / SnS / TiO2 photoanode prepared in the present invention has the strongest photocurrent response.
[0107] Electrochemical impedance spectroscopy tests were performed on different photoanodes. The results are shown in the attached figure. Figure 7 As shown in the attached Figure 7 The semicircle in the middle and high frequency part can reflect the electron transfer process in the electrode, and the diameter of the semicircle corresponds to the charge transfer resistance (Rct). The results show that the TiO2 photoanode has the largest charge transfer resistance, which is about 52Ω, and the Au / SnS / TiO2 photoanode has the smallest charge transfer resistance, which is about 20Ω, which means that the Au / SnS / TiO2 photoelectrode has excellent impedance performance. Figure 7 The upper right corner is the battery equivalent circuit, where R s Represents the external circuit resistance, C pe is the interface capacitance.
[0108] Furthermore, the above three photoanodes were used to assemble three dye-sensitive solar cells according to the operations of steps S2-S5, and performance tests were performed.
[0109] As attached Figure 8 The JV curves of natural dye-sensitized solar cells equipped with different photoanodes are shown. After testing, the following data can be obtained: the short-circuit current density (Jsc) of the DSSC equipped with TiO2 photoanode is 1.72mA / cm 2 , the open circuit voltage (Voc) is 330mV, the fill factor (FF) is 35.2%, and the photoelectric conversion efficiency (PCE) is 0.20%. After modifying the SnS nanoparticle layer, the short circuit current density (Jsc) of the corresponding photoanode is 1.92mA / cm 2 , the open circuit voltage (Voc) is 338mV, the fill factor (FF) is 43.1%, and the photoelectric conversion efficiency (PCE) is 0.28%. Compared with the DSSC equipped with pure TiO2 photoanode, the short circuit current increased by 11.6% and the photoelectric conversion efficiency increased by 40%, proving that SnS nanoparticles improve the performance of DSSC due to the larger light absorption range and smaller band gap under illumination, thereby generating more electrons and reducing electron recombination.
[0110] After modification with nano-Au, the short-circuit current density (Jsc) of the DSSC equipped with Au / SnS / TiO2 photoanode was further increased to 2.19 mA / cm 2, the open circuit voltage (Voc) is 350mV, the fill factor (FF) is 53.4%, and the conversion efficiency reaches 0.41%. Compared with the DSSC equipped with SnS / TiO2 photoanode, the photoelectric conversion efficiency is improved by 46%.
[0111] Furthermore, the dye-sensitive solar cell prepared by the preparation method of the present invention is compared with the existing dye-sensitive solar cell using a natural dye-sensitive anode, and the performance comparison results are shown in Table 1 below.
[0112] Table 1 Comparison results of the performance of the dye-sensitized solar cell in the present invention and other existing dye-sensitized solar cells
[0113]
[0114] In Table 1 above, [1] refers to the literature Surana K, Idris MG, Bhattacharya B. Natural dye extraction from Syzygium Cumini and its potential photovoltaic application as economical sensitizer [J]. Applied Nanoscience, 2020, 10(10): 1-7.
[0115] [2] Represents the literature Kbe A, Pyh A, Srs A, et al. Extraction of natural dye (specifically anthocyanin) from pomegranate fruit source and their subsequent use in DSSC[J].2021,43:2716-2720.
[0116] [3] Represented literature Al-Alwani M.Electrochemical Properties of NaturalSensitizer from Garcinia mangostana and Archidendron pauciflorum Pericarps for Dye-Sensitized Solar Cell (DSSC) Application[J]. Sains Malaysiana, 2020, 49(12): 3007-3015.
[0117] [4] Represents the literature Najm AS, Ludin NA, Abdullah MF, et al. Areca catechuextracted natural new sensitizer for dye-sensitized solar cell: Performance evaluation [J]. Journal of Materials Science: Materials in Electronics, 2020, 31(4): 3564-3575.
[0118] It can be seen from Table 1 above that the dye-sensitive solar cell prepared by the preparation method of the present invention still has performance advantages.
[0119] Embodiment 2:
[0120] The dye-sensitive solar cell based on the Au / SnS / TiO2 composite structure photoanode prepared in Example 1 is applied to the sunroof of an electric vehicle, and multiple dye-sensitive solar cells are spliced together and integrated into the original sunroof of the electric vehicle, as shown in the attached figure. Fig. 9 As shown, by virtue of the natural light transmittance and photovoltaic characteristics of dye-sensitive solar cells, it can not only realize the function of the original car sunroof but also charge electric vehicles in real time, greatly saving the original car charging time and charging costs.
[0121] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a dye-sensitive solar cell based on a composite structure photoanode, characterized in that: The following steps are included: S1: Preparation of Au / SnS / TiO2 composite structure photoanode; S2: preparing electrolyte solution; S3: preparing blueberry juice with natural dye; S4: preparing the counter electrode; S5: Assemble Au / SnS / TiO2 composite structure photoanode, electrolyte, natural dye and counter electrode into dye-sensitive solar cells; in, The specific operation of step S1 includes the following steps: S101: Clean the conductive glass and air-dry it for later use; S102: preparing titanium dioxide slurry, NaS solution, SnCl2 solution and Au nano solution for later use; S103: evenly spin-coat the titanium dioxide slurry onto the surface of the conductive glass, heat it to 400-500°C and calcine it for 2h at a heating rate of 6-8°C / min; S104: using NaS solution and SnCl2 solution, a SnS layer is prepared on the surface of the conductive glass coated with titanium dioxide slurry by a continuous ion layer adsorption reaction method; S105: using a dropper to evenly drop the Au nano-solution onto the conductive glass treated in step S104, and after natural air drying, annealing at 80-120°C for 2-5 minutes at a heating rate of 15-25°C / s, to finally obtain an Au / SnS / TiO2 composite structure photoanode; The specific operation of step S104 includes: immersing the conductive glass calcined in step S103 in a NaS solution for 1 minute, taking it out and rinsing it with deionized water for 5 seconds, and air-drying it at 60°C using a high-temperature blower; then immersing it in a SnCl2 solution for 1 minute, taking it out and rinsing it with deionized water for 5 seconds, and air-drying it at 60°C using a high-temperature blower; repeating the operation 4 times, and then annealing the air-dried conductive glass at 250°C for 3 minutes using a rapid annealing system, with a heating rate of 20°C / s; The specific operation of step S5 includes the following steps: S501: placing the Au / SnS / TiO2 composite structure photoanode prepared in step S1 in the natural dye prepared in step S3, soaking for 24 hours, taking it out and rinsing the surface of the Au / SnS / TiO2 composite structure photoanode with deionized water; S502: clamping the Au / SnS / TiO2 composite structure photoanode processed in step S501 and the counter electrode prepared in step S4 together with a clamp; S503: Use a pipette to absorb the electrolyte solution prepared in step S2, and inject it into the gap between the Au / SnS / TiO2 composite structure photoanode and the counter electrode, and wait for the electrolyte solution to diffuse into the entire gap space to complete the assembly of the dye-sensitive solar cell.
2. The method for preparing a dye-sensitive solar cell based on a composite structure photoanode according to claim 1, characterized in that: The method for preparing the titanium dioxide slurry described in step S102 comprises the following steps: S1021a: Accurately weigh 0.15g polyvinyl pyrrolidone powder and 0.3g P 25 -Put the TiO2 powder in a beaker and stir to mix the two solids evenly; S1022a: Add 1 mL of anhydrous ethanol and 1 mL of deionized water to the beaker in step S1021a, and stir with a glass rod until completely mixed to obtain titanium dioxide slurry.
3. The method for preparing a dye-sensitive solar cell based on a composite structure photoanode according to claim 1, characterized in that: The method for preparing the SnCl2 solution described in step S102 comprises the following steps: S1021b: Mix dihydrate SnCl2 and concentrated hydrochloric acid in a ratio of 1:5: S1022b: The mixed solution in step S1021b is continuously heated at a temperature of 100° C. until the solution changes from turbid to clear and transparent, and then deionized water is added to prepare a 0.01 mol / L SnCl2 solution.
4. The method for preparing a dye-sensitive solar cell based on a composite structure photoanode according to claim 1, characterized in that: The method for preparing the Au nano-solution described in step S102 comprises the following steps: S1021c: Accurately weigh 0.1 g of sodium citrate and add it to a beaker containing 10 mL of deionized water. Use a glass rod to stir until the sodium citrate is completely dissolved to obtain a sodium citrate solution. S1022c: Accurately weigh 0.01 g of solid tetrachloroauric acid, add it to a beaker containing 100 mL of deionized water, and heat to boiling while stirring; S1023c: Measure 2 mL of the sodium citrate solution in step S1021c, add it to the beaker in step S1022c, continue stirring and heating for 10 minutes, then remove the heat source and continue stirring for 15 minutes, cool to room temperature, and obtain an Au nano solution rich in Au nanoparticles.
5. The method for preparing a dye-sensitive solar cell based on a composite structure photoanode according to claim 1, characterized in that: The specific operation of step S2 includes the following steps: S201: Accurately weigh 0.635 g of iodine and add it to a beaker containing 10 mL of ethylene glycol, stirring until completely dissolved; S202: Accurately weigh 1.66 g of potassium iodide and add it to a beaker containing 10 mL of ethylene glycol, stirring until completely dissolved; S203: 1 mL of the solutions in steps S201 and S202 are measured respectively, and mixed to obtain an electrolyte solution.
6. The method for preparing a dye-sensitive solar cell based on a composite structure photoanode according to claim 1, characterized in that: The specific operation of step S4 includes the following steps: S401: ultrasonically clean the conductive glass using acetone, ethanol and deionized water respectively, and air dry; S402: A graphite layer is uniformly coated on the surface of the air-dried conductive glass to obtain a counter electrode.
7. A dye-sensitive solar cell prepared by the method for preparing a dye-sensitive solar cell based on a composite structure photoanode according to any one of claims 1 to 6.
8. Application of a dye-sensitive solar cell prepared by the method for preparing a dye-sensitive solar cell based on a composite structure photoanode according to any one of claims 1 to 6 in a sunroof of an electric vehicle.
Citation Information
Patent Citations
Preparation method of photo-anode of ZnS / Au / TiO2 nano composite film
CN102360958B
Preparation method of solar battery photoanode based on localized surface plasmon resonance (LSPR)
CN102231334A
Method for improving photoelectric conversion efficiency of dye-sensitized solar cell
CN103714977A